Medical and Legal Framework for the Prevention of Infectious Diseases in Georgia - Giorgi Shashiashvili; Nini Shashiashvili; Ana Tegetashvili (European Scientific Journal, ESJ, 2026)
The spread of infectious diseases constitutes a significant challenge to both individual and public health. This article examines the legislative regulations in force in Georgia, as well as the medical and legal processes and their effectiveness, particularly in the post–COVID-19 pandemic period. The aim of the article is to assess the effectiveness of these regulations, identify weaknesses and lessons learned during the pandemic, and evaluate their compliance with international practices and standards (WHO, 2005; Law of Georgia on Public Health, 2007; ECDC, n.d.; WHO/UN Georgia, 2020). Legal methods for the prevention of infectious diseases include the state’s authority to impose mandatory isolation and quarantine, ensure immediate dissemination of information, protect patients’ rights, restrict freedom of movement, and declare emergency regimes. Key components of medical procedures include epidemiological surveillance, disease detection and differentiated treatment, vaccination programs, laboratory infrastructure, public awareness initiatives, and the training of medical personnel (WHO, 2016; BMC Health Services Research, 2023). Recent pandemic experience in Georgia demonstrated that at the onset of the pandemic and during the first wave, strict restrictions and controls on public events were rapidly implemented, which slowed the early spread of the virus. Concurrently, it was identified that changes in the political environment, disruptions in communication strategies, and delays in the implementation of vaccination programs contributed to the intensification of disease transmission and created challenges related to scale and governance. Furthermore, monitoring of COVID-19 management revealed that the expansion of laboratory capacity, along with the mitigation of economic and socio-psychological impacts, represented significant challenges. Over time, biosurveillance systems were progressively strengthened, continuous genomic analysis of the virus was enhanced, and collaboration with public health emergency operations centers was reinforced.